Pemanfaatan Teknologi Blockchain Dalam Pengelolaan Dana Wakaf - Lutfia Salsabila; Mahira Fikriya; Farid Abdullah; Muhammad Affan (Jurnal Ekonomi dan Bisnis Digital, 2022)
In December 2011, a suspected case of misappropriation of a 2806 square meter waqf land occurred in Jombang. According to one resident, M. Nizar, the land had been dedicated as a waqf in 1987 for the Baitul Hikmah Education Foundation and the community mosque in Plandi village, Jombang sub-district, Jombang regency, East Java. This incident significantly eroded the community's trust in waqf fund management. The purpose of this research is to assess the substantial impact of blockchain technology on optimizing waqf fund management, particularly its implementation on the Finterra platform. The study employs a quantitative approach through path analysis, utilizing data obtained from relevant sources to support the discussion. The research findings indicate that blockchain technology has a significant influence on optimizing waqf fund management.